Evaluating the implementation of a hypertension program based on mHealth and community pharmacies integration to primary care centers at a municipality level in Argentina during the COVID-19 pandemic - Esandi, M. E.; Ortiz, Z.; Bernabei, V.; Villalba, N. B.; Liggio, S.; Della Maggiora, M.; García, N. A.; Bruzzone, A.; Blanco, G.; Prieto Merino, D.; Legido Quigley, H.; Perel, P. (Frontiers in Health Services, 2024)
IntroductionWhile pharmacists-led interventions in hypertension have proven effective in high-income countries, their implementation and impact in low- and middle-income countries (LMIC) remain limited. This study assessed the implementation and outcomes of the hypertension program FarmaTeCuida (FTC), which integrated community pharmacies into the public primary care level using information and communication technologies. The study took place during the pandemic in General Pueyrredón, Buenos Aires, Argentina, so modifications to the implementation strategy and expected outcomes were also analyzed.MethodsA mixed-methods study was conducted using the non-adoption, abandonment, scaling-up, dissemination, and sustainability (NASSS) conceptual model. Qualitative in-depth interviews were conducted with key stakeholders using snowball sampling until thematic saturation was achieved. The quantitative approach employed a quasi-experimental, prospective, longitudinal design in a cohort of hypertensive patients enrolled in the FTC program since October 2020 to March 2022. Adoption, access, adherence to follow-up, and blood pressure levels were assessed. Clinical outcomes were compared to a cohort of hypertensive patients attending primary health care centers (PHCCs) in 2021 but not enrolled in the FTC program. Routine data from this cohort was obtained from the municipal health information system (HIS).ResultsOut of 33 PHCCs, 23 adopted the FTC program, but only four collaborated with community pharmacies. A total of 440 patients were recruited, with 399 (91%) enrolled at PHCCs. Hypertension was detected in 63% (279/440) of cases at the first visit (113 were possible hypertensive patients; 26 new hypertensive patients and 140 already diagnosed). During follow-up, FTC identified 52 new hypertensive patients (12% out of 440). Reduction of systolic blood pressure (SBP) was observed in patients enrolled in both the FTC program and the comparison group over 60 days. In the multivariate analysis that included all hypertensive patient (FTC and HIS) we found strong evidence that for each month of follow up, SBP was reduced by 1.12 mmHg; however, we did not find any significant effect of the FTC program on SBP trend (interaction FTC*months has a p-value = 0.23). The pandemic was identified as the main reason for the program's underperformance; in addition we identified barriers related to technology, patient suitability, implementation team characteristics, and organizational factors.DiscussionOur study, grounded in the NASSS model, highlights the profound complexity of introducing innovative strategies in low- and middle-income settings. Despite substantial challenges posed by the pandemic, these obstacles provided valuable insights, identified areas for improvement, and informed strategies essential for reshaping the care paradigm for conditions like hypertension in resource-constrained environments.